Academic and Technical Vocabularies of Management Studies in Abstracts Published in Reputable Journals - Murniati, Murniati (Journal of English Language and Culture, 2018)
This research aims to find the academic vocabularies as well as the technical vocabularies in abstracts published in reputable journals. The topics of the abstracts are retail, marketing, human resource, finance, and strategic management. Those topics are chosen since those five topics are the streams in Bunda Mulia University under Management Departments. Moreover, there is a corpus based program named wordandphrase.info to analyze both academic and technical vocabularies in those five topics. The data is gained from abstracts published in reputable journals retrieved from www.sciencedirect.com. The results show that the percentage of the top 1-500 academic words used in abstract is from 20% to 30%. Regarding the next 500 - 3.000 academic words list, the range of those words used is between 7% to 10%. The range of the technical vocabularies is, however, different from one topic to another. The range of technical vocabularies in retail and marketing is about 5%, while in finance, human resource and strategic management, the range is between 0.4 to 2%. Keywords:  academic vocabularies, technical vocabularies, business